Antibacterial action of slightly acidic electrolytic water against Cronobacter sakazakii and its application as a disinfectant on high-risk contact surfaces - Guo, Ling; Han, Jing; Wang, Yanyan; Chang, Yajing; Qu, Wenxuan; Man, Chaoxin; Fei, Peng; Jiang, Yujun (Frontiers in Microbiology, 2024)
Powdered infant formula (PIF) is prone to Cronobacter sakazakii (C. sakazakii) contamination, which can result in infections that endanger the lives of newborns and infants. Slightly acidic electrolytic water (SAEW) has shown antibacterial effects on a variety of foodborne pathogens and has a wide applicability in the food industry. Here, the antibacterial activity of SAEW against C. sakazakii and its use as a disinfectant on contact surfaces with high infection transmission risk were investigated. The inactivation of SAEW on C. sakazakii was positively correlated to the SAEW concentration and treatment time. The antibacterial effect of SAEW was achieved by decreasing the intracellular adenosine triphosphate (ATP), K + , protein, and DNA contents of C. sakazakii, reducing the intracellular pH (pHin) and destroying the cell morphology, which led to inactivation of C. sakazakii ultimately. To test the applicability of this study, the results showed that approximately 10 3 CFU/cm 2 of C. sakazakii were successfully inactivated on stainless steel and rubber surfaces after a 30 mg/L SAEW treatment for 20 s. These results indicate the antibacterial mechanism and potential application of SAEW against C. sakazakii, as well as a new strategy for the prevention and control of C. sakazakii on stainless steel and rubber surfaces. This is a provisional file, not the final typeset article Cronobacter sakazakii Cronobacter sakazakii (C. sakazakii) is a Gram-negative and non-sporeforming bacterium classified to the Enterobacteriaceae, which is an opportunistic foodborne pathogen.